2006
DOI: 10.1002/app.24438
|View full text |Cite
|
Sign up to set email alerts
|

Studies on blends of natural rubber and ethylene propylene diene rubber modified with phosphorylated cardanol prepolymer: Processability, physico‐mechanical properties, and morphology

Abstract: ABSTRACT:The melt processability and physico-mechanical properties of blends of natural rubber (NR) and ethylene propylene diene rubber (EPDM) containing different dosages (0-10 phr) of phosphorylated cardanol prepolymer (PCP) were studied in unfilled and china-clay-filled mixes. The plasticizing effect of PCP in the blends was evidenced by progressive reduction in power consumption of the mixing and activation energy for melt flow with an increase in the dosage of PCP. The PCP-modified blend vulcanizates show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The basic materials used in this study were a commercial grade polyamide1010 (PA1010, 11) with a density of 1.03-1.05 g/cm 3 After the mixing, pieces of these blends were taken out of the mixer and put into ice-water to freeze the original structure for the observation in a scanning electron microscope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic materials used in this study were a commercial grade polyamide1010 (PA1010, 11) with a density of 1.03-1.05 g/cm 3 After the mixing, pieces of these blends were taken out of the mixer and put into ice-water to freeze the original structure for the observation in a scanning electron microscope.…”
Section: Methodsmentioning
confidence: 99%
“…During the past few decades, many research groups carried out corresponding studies to gain a better understanding of morphology and good results were found. [1][2][3][4][5][6] It is well known that when two immiscible/imcompatible polymers are blended, one phase will mechanically disperse into the other and form the dispersed phase, while the other becomes the continuous phase. In general, the particle size of the minor phase depends greatly on the composition, the viscoelasticity of the constituent components, the shear stress/rate and the interfacial tension between phases.…”
Section: Introductionmentioning
confidence: 99%
“…And cardanol can improve the resistance to degradation, bacteria, termites and recession of materials. Cardanol can also improve the chemical and physical properties when applied as plasticizer of rubber . In the market, the plasticizer of polyvinyl chloride (PVC) accounts for the bulk of the total output.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the blends of NR and EPDM would theoretically exhibit combined properties, i.e., good thermal–ozone resistance in conjunction with good tack, mechanical, and dynamic properties 7. However, since the NR/EPDM blend is thermodynamically incompatible, the selection of a suitable vulcanizing system and the addition of a suitable homogenizing agent could significantly improve the homogeneity of the rubber blends, leading to the enhancement in properties of the blend vulcanizates 6, 8–11…”
Section: Introductionmentioning
confidence: 99%
“…7 However, since the NR/EPDM blend is thermodynamically incompatible, the selection of a suitable vulcanizing system and the addition of a suitable homogenizing agent could significantly improve the homogeneity of the rubber blends, leading to the enhancement in properties of the blend vulcanizates. 6,[8][9][10][11] In this work, the in-house developed intermeshing co-rotating batch mixer and a tangential counterrotating batch mixer were utilized to prepare 60/40 NR/EPDM blends. The phase morphology of NR/ EPDM blends from both mixers was compared.…”
Section: Introductionmentioning
confidence: 99%